2009
DOI: 10.1523/jneurosci.2167-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based MRI Probes for Specific Detection of Chronic Exposure to Amphetamine in Living Brains

Abstract: We designed phosphorothioate-modified DNA probes linked to superparamagnetic iron oxide nanoparticles (SPION) for in vivo magnetic resonance imaging (MRI) of fosB and ⌬fosB mRNA after amphetamine (AMPH) exposure in mice. Specificity of both the fosB and ⌬fosB probes was verified by in vitro reverse transcriptase-PCR amplification to a single fragment of total cDNA obtained from acutely AMPH-exposed mouse brains. We confirmed time-dependent uptake and retention profiles of both probes in neurons of GAD67-green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Although several other IEG promoters recently became popular markers of neuronal activity, the c-fos promoter is commonly used to validate findings. While the majority of imaging-based studies have focused on optical markers to monitor c-fos gene regulation, it should be noted that other means, such as magnetic resonance imaging (MRI), have been used to non-invasively monitor c- fos (Liu et al, 2007) and fosB mRNA in vivo (Liu et al, 2009). It has been suggested that genetically encoded reporters designed for MRI (Gilad et al, 2007; Bar-Shir et al, 2013), and driven by the c-fos promoter, can be applied for the real-time monitoring of gene expression in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although several other IEG promoters recently became popular markers of neuronal activity, the c-fos promoter is commonly used to validate findings. While the majority of imaging-based studies have focused on optical markers to monitor c-fos gene regulation, it should be noted that other means, such as magnetic resonance imaging (MRI), have been used to non-invasively monitor c- fos (Liu et al, 2007) and fosB mRNA in vivo (Liu et al, 2009). It has been suggested that genetically encoded reporters designed for MRI (Gilad et al, 2007; Bar-Shir et al, 2013), and driven by the c-fos promoter, can be applied for the real-time monitoring of gene expression in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…We then co-stained Cy2-labeled rabbit polyclonal IgG against glial fibrillary acidic protein (GFAP, Z0334, Dako) or Cy3-labeled polyclonal IgG against ionized calcium-binding adaptor molecule 1 (IBA1, ab5076, Abcam); we used Cy2-labeled monoclonal IgG against NeuN (A60, Millipore) or Cy3-labeled goat IgG against GFAP (clone C-19, Santa Cruz) for progenitor cells. Nucleic acids were stained with DAPI (1:500 dilution) [18]. To examine HDAC5 mRNA expression using Cy3-sODN (see below), transgenic mice ( n  = 3) underwent icv puncture 1 week before they were administered Cy3-sODN (120 pmol in 0.1 ml, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Four hours after amphetamine administration we obtained brain samples and froze them by slow cooling with liquid nitrogen. After staining slices of brain tissue (25 μm in thickness) with 0.5% Hoechst for nucleic acid, we obtained photographs using the same technique and equipment described above [18]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the GABAergic system is also modified by Ket or Amph in the motor cortex, somatosensory cortex, and striatum [12,21,22]. The key enzyme of GABA synthesis, glutamate decarboxylase 67 (GAD 67 ), is commonly used as a biomarker for GABAergic neurons, and certain properties of GAD 67 -positive cells are altered by Ket or Amph treatments [23,24]. The interplay of the two drugs in different neurotransmission systems thus warrants detailed study.…”
Section: Introductionmentioning
confidence: 99%